Co‐Atomic Interface Minimizing Charge Transfer Barrier in Polytypic Perovskites for CO2 Photoreduction - Fengyi Zhong; Jianping Sheng; Chenyu Du; Ye He; Fengying Zhang; Yanjuan Sun; Ying Zhou; Fan Dong (Advanced Science)
Abstract Heterojunctions, known for their decent separation of photo‐generated electrons and holes, are promising for photocatalytic CO2 reduction. However, a significant obstacle in traditional post‐assembled heterojunctions is the high interfacial barrier for charge transfer caused by atomic lattice mismatch at multiphase interfaces. Here, as research prototypes, the study creates a lattice‐matched co‐atomic interface within CsPbBr3‐CsPb2Br5 polytypic nanocrystals (113‐125 PNs) through the proposed in situ hybrid strategy to elucidate the underlying charge transfer mechanism within this unique interface. Compared to CsPbBr3 nanocrystals, the 113–125 PNs exhibit a remarkable 3.6‐fold increase in photocatalytic CO2 reduction activity (173.3 µmol−1 g−1 within 5 h). Furthermore, Kelvin probe force microscopy results reveal an increase in the built‐in electric field within this lattice‐matched co‐atomic interface from 43.5 to 68.7 mV, providing a stronger driving force for charge separation and directional migration. Additionally, ultrafast transient absorption spectroscopy uncovers the additional charge carrier transfer pathways across this lattice‐matched co‐atomic interface. Thus, this unique co‐atomic interface significantly promotes the interfacial electronic coupling and mitigates the charge transfer barrier, thus facilitating efficient charge separation and transfer. These insights underscore the importance of interfacial structure in heterojunction design and comprehending the intricate interplay between interface and carrier dynamics.